2020
DOI: 10.1002/aic.16980
|View full text |Cite
|
Sign up to set email alerts
|

Operable adaptive sparse identification of systems: Application to chemical processes

Abstract: Over the past few decades, several data-driven methods have been developed for identifying a model that accurately describes the process dynamics. Lately, sparse identification of nonlinear dynamics (SINDy) has delivered promising results for various nonlinear processes. However, at any instance of plant-model mismatch or process upset, retraining the model using SINDy is computationally expensive and cannot guarantee to catch up with rapidly changing dynamics. Hence, we propose operable adaptive sparse identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…They used sparse regression in combination with feature selection to identify accurate models in an adaptive model identification methodology which requires much less than data that current methods. In a similar study Bhadiraju et al 121 have developed a modified SINDy approach that is helpful in cases of plant model mismatch and does not require retraining and hence computationally less expensive.…”
Section: Science Compliments MLmentioning
confidence: 99%
“…They used sparse regression in combination with feature selection to identify accurate models in an adaptive model identification methodology which requires much less than data that current methods. In a similar study Bhadiraju et al 121 have developed a modified SINDy approach that is helpful in cases of plant model mismatch and does not require retraining and hence computationally less expensive.…”
Section: Science Compliments MLmentioning
confidence: 99%
“…In this article, we discuss an alternative non-linear method for the cases in which the resulting series is not stationary. Although we find many emerging non-linear techniques that can be used to make both short-term and long-term predictions on non-stationary chaotic data, such as the sparse identification of nonlinear dynamics (SINDy) algorithm [11] widely used to model non-linear dynamic systems and make predictions on them [12][13][14][15], or non-linear systems reconstruction techniques that allow the regeneration of time series subjected to white noise, which would allow a new study of stationarity and eliminate the disturbances associated with the observed variable [16,17], in this work, we focus on maximal Lyapunov exponents.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, regression techniques are more proper for providing the interpretability that NN does not have, which makes them an attractive tool to extract dynamic evolution laws from datasets [13]. In this scenario, stands out the technique known as sparse identification of nonlinear dynamical systems (SINDy) [13][14][15][16], a sparse regression method to identify evolution equations from data that proven to be efficient in different areas and problems, and stands out for three aspects: (i) interpretability of the obtained equation; (ii) excellent generalization (extrapolation) capability; (iii) computational efficiency. As several dynamic systems have evolution laws with only a few terms, SINDy looks for a sparse and parsimonious differential equation that best fits the known data.…”
Section: Introductionmentioning
confidence: 99%